The religious traditions of Japan, 500-1600 - Bowring, Richard John 1947- (Cambridge University Press, 2005)
"The Religious Traditions of Japan, 500-1600, describes in outline the development of Japanese religious thought and practice from the introduction of writing to the point at which medieval attitudes gave way to a distinctive pre-modern culture, a change that brought an end to the dominance of religious institutions. A wide range of approaches using the resources of art, history, social and intellectual history, as well as doctrine, is brought to bear on the subject. It attempts to give as full a picture as possible of the richness of the Japanese tradition as it succeeded in holding together on the one hand, Buddhism, with its sophisticated intellectual structures, and on the other hand the disparate local cults that eventually achieved a kind of unity under the rubric of Shinto. Much of this book is concerned with the way in which Buddhism used the local cults to consolidate its position of hegemony while at the same time offering an example against which Shinto could slowly invent itself. An understanding of this process of constant and at times difficult interaction is essential to a deeper appreciation of Japan's history and its cultural achievements."--BOOK JACKET.